Gerda Walther’s Phenomenology of Sociality, Psychology, and Religion edited by A. Calcagno - Evrard, Renaud (Journal of Scientific Exploration, 2020)
This book is part of a Springer series on Women in the History of Philosophy and Sciences that attempted to balance sexism in science and the so-called “Matilda” effect (denial or minimization of the scientific contribution of women researchers to the benefit of their male colleagues). I’m clearly not a specialist in the deep philosophical work discussed by the contributors of this book, and thus will not give a fully technical review, but I was strongly curious to learn more about Gerda Walther (1897-1977). Indeed, she was for me the famous “secretary of the Baron von Schrenck-Notzing” (1862-1929), one of the main psychical researchers of the modern era (Mulacz, 2013; Sommer, 2012; Wolffram, 2006). For my own historical research (Evrard, 2016), I read a lot of correspondence between Walther and members of the Institut métapsychique international in the archives of this French research group and in the archives of the Institut für Grenzgebiete der Psychologie und Psychohygiene in Freiburg-im-Breisgau. But I didn’t have any clue about the wide dimension of this character and her importance for the history of philosophy as a brilliant student and continuator of Edmund Husserl. The book provides probably the best overview of her life and philosophy. In the first part “The life and work of Gerda Walther”, Rodney Parker gives “a sketch of her life” (3-9); and Marina Pia Pellegrino writes about the general orientation of her phenomenological approach of “traces of lived experiences” (11-24).